Nuclear membrane ruptures, cell death, and tissue damage in the setting of nuclear lamin deficiencies. Issue 1 (1st January 2020) - Chen, Natalie Y.; Kim, Paul H.; Fong, Loren G.; Young, Stephen G.
ABSTRACT: The nuclear membranes function as a barrier to separate the cell nucleus from the cytoplasm, but this barrier can be compromised by nuclear membrane ruptures, leading to intermixing of nuclear and cytoplasmic contents. Spontaneous nuclear membrane ruptures ( i.e ., ruptures occurring in the absence of mechanical stress) have been observed in cultured cells, but they are more frequent in the setting of defects or deficiencies in nuclear lamins and when cells are subjected to mechanical stress. Nuclear membrane ruptures in cultured cells have been linked to DNA damage, but the relevance of ruptures to developmental or physiologic processes in vivo has received little attention. Recently, we addressed that issue by examining neuronal migration in the cerebral cortex, a developmental process that subjects the cell nucleus to mechanical stress. In the setting of lamin B1 deficiency, we observed frequent nuclear membrane ruptures in migrating neurons in the developing cerebral cortex and showed that those ruptures are likely the cause of observed DNA damage, neuronal cell death, and profound neuropathology. In this review, we discuss the physiologic relevance of nuclear membrane ruptures, with a focus on migrating neurons in cell culture and in the cerebral cortex of genetically modified mice.